Investigating the role of audit time pressure on dividend quality in companies listed in Stock Exchange of Tehran - Sourmeiy, Soulmaz (2022)
The present study investigated the role of audit time pressure on dividend quality in listed companies in Stock Exchange of Tehran. Auditors are often pressured to set time budgets. Due to the increasing importance of audit firms for achieving time budgets as a measure of effectiveness, their difficulties in measuring audit effectiveness, the potential conflict between doing the right things and control costs for high quality audits have intensified. In order to study the aforementioned subject, the statistical population of the audit firms of the member of the Society of Certified Public Accountants within the city of Tehran was determined and the required data were collected from these institutes by random sampling. Durbin–Watson statistic method and correlation with Eviews software were also used to test the research hypotheses. The results indicated that audit time pressure has a significant effect on dividend quality.